Developing Academic Literacies in Medicine and Agriculture: The Design, Delivery and Evaluation of Blended Learning Support for Research Writing in English - Corbett, John Blair (The ESPecialist, 2020)
The growth of English as a scientific lingua franca and the pressure to raise the international ranking of Brazilian universities have increased the demand for English language support to develop academic literacies amongst local researchers, particularly in areas such as writing journal articles for international publication. The challenges to delivering targeted support for the development of such literacies include limited curricular space, clashing timetables, and the fact that single institutions often have geographically dispersed campuses. Blended learning offers a possible means of addressing these challenges in the flexibility afforded by course delivery that is partly face-to-face and partly online and asynchronous. This paper reports on the design, delivery and evaluation of courses in research article writing delivered to postgraduate students in the Faculty of Medicine and School of Agriculture at the University of Sao Paulo in 2018-19. The paper confirms that the blended learning format can be a successful means of enhancing academic literacies, while identifying those areas that are easier and more difficult to teach, and which aspects of the research article genre cause novice graduate writers specific problems.